Faktor-faktor Remaja Putus Sekolah Di Kelurahan Teluk Kabung Utara Kota Padang - Fatmawati, Yulia; Sano, Afrizal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is based on the presence of a number of teenagers who drop out of school in the North Teluk Kabung Subdistrict, Padang City. Some of the teenagers appear to help parents fulfill their daily needs such as fishing and the conditions of life and adolescence are not conducive. This type of research is field research and qualitative methods, the technique of determining respondents is the snowball sampling technique. Data collection techniques through observation and interviews. Data were analyzed by step data reduction, data presentation and drawing conclusions. The respondents of this study were eleven people. The results showed that the factors that caused adolescents to drop out in the area were, low learning ability and lazy repetition, insufficient school fees, staying in class and not passing the National Examination (National Examination), lack of attention from parents, bullying by friends, student attitudes toward the teacher, and the presence of students during learning (leaving class while studying).